#African Time: Making the Future Legible. Issue 3 (2nd October 2021) - Widlok, Thomas; Knab, Joachim; van der Wulp, Christa
ABSTRACT: The notion that Africans lack a sense of future was extensively debated following John Mbiti's African Religions and Philosophy (1969) and has since entered the scholarly and popular discourse as a fixed topos which we label #African time ('Europeans have watches, Africans have time'). The most recent references to the topos are found in future vision reports of many African states and non-governmental organisations (NGOs) that assert and demand a sense of future for Africa and from members of African societies. While the notion of a homogenised past-oriented 'African time' has been largely abandoned in academia, #African time appears to be an accepted and enactable popular discourse among policy makers, state planners and NGO workers. This article provides examples of this phenomenon and it extends James Scott's (1998) idea, that state authorities tend to make its citizens 'legible' in order to govern them, to explain the tenaciousness of the #African time topos. While Scott's examples are almost exclusively about shaping space for legibility, we show that there is a similar process taking place with regards to time, and that citizens, communities and societies are expected to formulate visions for the future if they want their interests to be 'read' by the state, by NGOs, donor agencies and other powerful agents they interact with. In this process of making the future visions of citizens legible, the topos of #African time plays a major role.